The Effect of Organizational Climate, Teachers' Professionalism, and Achievement Motivation on Teachers' Performance at State Private School - Muhammad Rizky; Candra Wijaya; Muhammad Rifa'i (Universitas Pahlawan Tuanku Tambusai, 2022)
This study aims to analyze the effect of organizational climate, teacher professionalism, and achievement motivation on teacher performance in State Elementary Schools throughout Sawit Seberang District, Langkat Regency. Teachers are one of the elements in the field of education who participate actively and place their position as professionals to be able to improve the quality of education in Indonesia in order to get out of educational problems. However, in reality, the quality of education in Indonesia is still problematic. The influence of organizational climate can affect the professionalism of teachers so that they can have a significant influence on the condition of teacher performance. This research was conducted using quantitative methods with the data analysis technique used is inferential statistical techniques. Based on the results of the study, it can be concluded as follows: (1) The tendency level of organizational climate in SD Negeri Sawit Seberang District, Langkat Regency is still in the poor category. (2) The level of tendency of teacher professionalism in SD Negeri Sawit Seberang District, Langkat Regency is still in the fairly good category. (3) The tendency level of the achievement motivation of teachers in SD Negeri Sawit Seberang District, Langkat Regency is still in the category of lacking achievement motivation. (4) The level of trend of teacher performance in SD Negeri Sawit Seberang District, Langkat Regency is still in the poor category.